The anatomical properties of Salvia section (Lamiaceae) in central district of Mardin (Turkey) and their taxonomic implications - Murat Kılıç; Fatma Mungan Kılıç (Journal of Advanced Research in Natural and Applied Sciences)
In this study, 4 Salvia species found in the Salvia section distributed in the Artuklu districtof Mardin province were analyzed comparatively in terms of anatomy. Plant specimens of Salviasection were collected from 11 localities. Anatomical studies were performed on specimens preservedin 70% alcohol. Transverse sections taken from the roots, stems, leaves, and petioles of the specieswere examined under a light microscope for anatomical examination. The anatomy of S. bracteata, S.macrochlamys, S. suffruticosa, S. trichoclada species were examined. The S. suffruticosa species wasexamined in detail for the first time anatomically. The data obtained as a result of the researches werecompared with the previous studies on the Salvia section. In anatomical examinations, it was observedthat the root, stem, leaf, and petiole structures of the taxa were similar but shapes and measurementsin addition to this the number of tissue layers and pith rows are different. Also anatomically analyses,it has been seen that hairiness formed a difference between some species. As a result of all thesediscussed data, the anatomical characters such as number of ray rows in root, number of collenchymalayers in stem, mesophyll structures in leaves, shape of midrib and number of vascular bundles inpetiole, provide important taxonomic information.